On the need of providing tooth morphology in descriptions of extant elasmobranch species - Guinot, Guillaume; Adnet, Sylvain; Shimada, Kenshu; Shimada, Kenshu; Underwood, Charlie J.; Siversson, Mikael; Ward, David J.; Kriwet, Jürgen; Cappetta, Henri (Zootaxa, 2018)
Elasmobranchii is a clade of chondrichthyans (cartilaginous fishes) that comprises sharks, skates and rays represented today by approximately 1,200 species. Chondrichthyans have a long evolutionary history dating back to the Late Ordovician (ca. 450 million years ago [Mya]) based on isolated dermal denticles (Janvier 1996). Other remains such as articulated skeletons and teeth are known from the Lower Devonian (ca. 410 Mya: Mader 1986; Miller et al. 2003). The fossil record of modern elasmobranchs (Neoselachii) can be traced back to the Early Permian (ca. 290 Mya) and is represented by isolated teeth (Ivanov 2005), with fossils of crown group sharks and rays appearing in Lower Jurassic (ca. 200 Mya) rocks (e.g., Cappetta 2012). Since their appearance in the geological record, elasmobranchs are mainly represented by isolated teeth, whereas articulated skeletons are very rare and restricted to a small number of fossil localities (e.g., Cappetta 2012). The scarcity of skeletal remains in their fossil record is due to their poorly mineralized cartilaginous skeleton that requires special taphonomical conditions to be preserved. Elasmobranch teeth, in contrast, are composed of highly mineralized tissues (hydroxyapatite) that have a strong preservation potential (Shimada 2006). In addition, elasmobranchs replace their teeth continuously over the course of their life span (polyphyodonty) and therefore shed thousands of teeth in their lifetime (Reif et al. 1978; Schnetz et al. 2016) leading to large numbers of potential fossils. These morphologically highly diverse isolated teeth constitute much of the rich fossil record of elasmobranchs, and largely form the basis of our understanding of elasmobranch diversity and evolution through geological time.